Compendium on the Study of Rural Electrification Programme-1977-78 - Planning Commission (Planning Commission, 1978)
Rural electrification has an important role to play in bringing about technological changes in agriculture, in stimulating the growth of agro-based small and medium-sized industries in rural areas, besides effecting changes in the social and cultural lives of the People in villages in the direction of modern living. It was only after independence that rural electrification began receiving some degree of attention when the responsibility for power generation, transmission -and distribution was taken over by the Government , and state Electricity Boards were formed under the Electricity Supply Act of 1948. Even so, the progress remained tardy for many years, on account of paucity of resources and a relatively low priority for programmes of rural electrification.
Government of India Programme Evaluation Organisation Planning Commission New Delhi